Nicotine metabolite ratio: Comparison of the three urinary versions to the plasma version and nicotine clearance in three clinical studies. (1st June 2021) - Giratallah, Haidy K.; Chenoweth, Meghan J.; Addo, Newton; Ahluwalia, Jasjit S.; Cox, Lisa Sanderson; Lerman, Caryn; George, Tony P.; Benowitz, Neal L.; Tyndale, Rachel F.
Highlights: Nicotine metabolism, mediated by CYP2A6, is proxied by the nicotine metabolite ratio (NMR) and can alter smoking behaviors. Versions of urinary NMRs (i.e. using free vs. glucuronidated metabolites) were compared to plasma NMR, and nicotine clearance. The urinary NMR version with total cotinine had the least utility; it is influenced by variation in cotinine glucuronidation. Knowing limitations of the different urinary NMRs has major implications for studying smoking behaviors and related diseases. Abstract: Background: Variation in CYP2A6 activity influences tobacco smoking behaviors and smoking-related health outcomes. Plasma Nicotine Metabolite Ratio (NMR) is a robust phenotypic biomarker of CYP2A6 activity and nicotine clearance. In urine, the NMR has been calculated as a ratio of free trans-3'-hydroxycotinine to free cotinine (NMRF/F ), total trans-3'-hydroxycotinine to free cotinine (NMRT/F ), or total trans-3'-hydroxycotinine to total cotinine (NMRT/T ). We evaluated these three urinary NMR versions relative to plasma NMR and nicotine clearance and elucidated mechanisms of discrepancies among them. Methods: Baseline plasma and urine biomarker data were available from two smoking cessation clinical trials and one nicotine pharmacokinetic study (total N = 768). NMRs were compared using Pearson correlations, linear regressions and ANOVA analyses. UGT2B10 and UGT2B17 were genotyped. Results: Urinary NMRT/F was the most highly related to plasma NMR (R 2 = 0.70, P <2.2e-16) followed by NMRF/F (R 2 = 0.68, P <2.2e-16), while NMRT/T was less strongly related (R 2 = 0.60, P <2.2e-16); consistent across study, ethnicity, sex, heaviness of smoking, and analyte analysis. Controlling for cotinine glucuronidation, as a phenotype or UGT2B10 genotype, corrected the NMRT/T discordance with plasma NMR (Panova <0.001). Similar findings were obtained for relationships of nicotine clearance with plasma NMR > urinary NMRT/F > NMRF/F > NMRT/T (R 2 = 0.41 > 0.37 > 0.35 > 0.25 respectively). Conclusion: Urinary NMRT/F followed by NMRF/F are the best urinary alternatives to plasma NMR or nicotine clearance. NMRT/T has the least utility as it is influenced substantially by variation in cotinine glucuronidation. Impact: This work highlighted the variation in urinary NMRs, and identified mechanisms for disparities among them, which facilitates their use in predicting smoking-related outcomes.